OP0025 Results from a multicenter, international, randomized, double-blind, placebo-controlled, phase 2 study of sirukumab, a human anti-IL-6 monoclonal antibody, in patients with active rheumatoid arthritis despite methotrexate therapy. (23rd January 2014) - Hsu, B.; Sheng, S.; Weinblatt, M.E.; Smolen, J.S.
Abstract : Objectives: To assess remission rates from a phase 2 study of sirukumab, a human monoclonal antibody against the cytokine interleukin-6 (formerly named CNTO 136), using the new provisional 2011 ACR/EULAR rheumatoid arthritis (RA) remission criteria. Methods: In the dose-ranging part of a 2-part, multicenter, randomized, double blind, placebo controlled, phase 2 study, pts with active RA despite methotrexate (MTX) were randomized equally to receive SC injections of placebo q2w at wks 0-10 and sirukumab 100 mg q2w at wks 12-24 (n=30), sirukumab 100 mg q2w at wks 0-24 (n=30), sirukumab 100 mg q4w at wks 0-24 (n=30), sirukumab 50 mg q4w at wks 0-24 (n=30), or sirukumab 25 mg q4w at wks 0-24 (n=31). RA remission rates were prospectively assessed using the DAS28 (CRP) remission criteria and retrospectively assessed using the 2011 ACR/EULAR remission criteria (Boolean-and SDAI-based) at wks 12, 24, and 38. The 2011 ACR/EULAR remission criteria used in this study were: Boolean-based (68-joint TJC ≤1, 66-joint SJC ≤1, CRP ≤1 mg/dL, PGA ≤1 on a 1-10 cm VAS), index-based (SDAI score [ie, 28-joint TJC + 28-joint SJC + PGA + physician's global assessment + CRP mg/dL] ≤3.3). Results: At wk 12 (pre-crossover), more pts were in remission with sirukumab than with placebo according to both Boolean- and SDAI-based ACR/EULAR criteria (2% vs 0% and 6% vs 3%, Table). The percentage of pts in remission according to all 3 criteria increased to a peak at wk 24 in the sirukumab 100 mg q2w and q4w treatment groups and remained higher than wk-12 rates at wk 38, 14 wks after the last dose of sirukumab. Pts who received sirukumab 100 mg q2w throughout the study achieved the highest remission rates according to all 3 remission criteria at all time points, including a statistically significant difference compared with placebo according to DAS28 remission criteria at wk 12 (20% vs 0%, p=0.024) and Boolean-based ACR/EULAR remission in 4/30 (13%) pts and SDAI-based ACR/EULAR remission in 7/30 (23%) pts at both wk 24 and wk 38. As expected, the more stringent 2011 ACR/EULAR remission criteria resulted in generally lower remission rates than the DAS28 remission criteria at all time points. Lower remission rates were seen for all groups at all time points with the Boolean-based vs the SDAI-based definition. Conclusions: Higher remission rates according to both the 2011 ACR/EULAR and the DAS28 (CRP) criteria were achieved with sirukumab at SC dose regimens ranging from 25-100 mg q2w-q4w compared with placebo. After placebo crossover to sirukumab, all groups achieved increasing remission rates over time with continued sirukumab treatment. The highest sirukumab dose regimen (100 mg q2w) achieved the highest remission rates. The 2011 ACR/EULAR criteria were more stringent than the DAS28 (CRP) criteria; and the Boolean-based definition was more stringent than the SDAI-based definition. Disclosure of Interest: B. Hsu Employee of: Janssen Research & Development, LLC, S. Sheng Employee of: Janssen Research & Development, LLC, M. Weinblatt Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, J. Smolen Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study